(untitled) (Jurnal Destinasi Pariwisata, 2025)
Oceanarium XYZ is a newly established artificial tourism destination located in South Tangerang, offering both educational and recreational experiences for its visitors. In the midst of competition with similar attractions such as Jakarta Aquarium Safari and SeaWorld Ancol, it is essential for management to understand the factors that influence visitors’ decision-making processes. This study aims to analyze the effect of the marketing mix elements product, price, place, and promotion on visiting decisions, and to identify which element contributes the most significantly. The results indicate that the marketing mix variables collectively have a significant influence on visitors’ decisions. Partially, the promotion variable has the most dominant effect, particularly through the effectiveness of digital promotion and social media campaigns in attracting visitor interest. Conversely, the price variable shows the weakest influence, suggesting that visitors prioritize the value of the overall experience over cost considerations. These findings offer strategic implications for Oceanarium XYZ management in developing more targeted and adaptive marketing strategies. Moreover, this study contributes academically as a reference for further research on tourism marketing, especially in the context of artificial tourism destinations.